]MA[ – The Space between the Interval - Bolles, Dylan; Evans, Keith; O'Kane, Suki; Schocker, Edward (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2024)
“]MA[ – The Space between the Interval” is the fourth movement of ]MA[, a multidisciplinary performance created in 2013 by Thingamajigs Performance Group (TPG) and performed at the UC Berkeley Art Museum and Pacific Film Archive. In 2019, group member Dylan Bolles conducted and recomposed a series of interviews in which TPG reflected on the process of making and performing ]MA[. We asked questions such as: How does embodiment create particular amalgamations of influence and technique that trouble distinctions between thoughts of East and West? How do cultural artifacts change when passed through different bodies and contexts? What are the underlying principles which allow for sometimes effortless musical communication between seemingly distant cultural representatives? Our conversations, disjointed as they are, intermingle both shared and previously unshared experiences from many years working together and apart on intercultural performance projects. What emerges is a glimpse into a process of intercultural integration in motion.